2021
DOI: 10.1093/mnras/stab014
|View full text |Cite
|
Sign up to set email alerts
|

The Three Hundred project: the gas disruption of infalling objects in cluster environments

Abstract: We analyse the gas content evolution of infalling haloes in cluster environments from The Three Hundred project, a collection of 324 numerically modelled galaxy clusters. The haloes in our sample were selected within 5R200 of the main cluster halo at $z$ = 0 and have total halo mass M200 ≥ 1011h−1M⊙. We track their main progenitors and study their gas evolution since their crossing into the infall region, which we define as 1–4R200. Studying the radial trends of our populations using both the full phase-space … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 52 publications
(90 reference statements)
4
30
1
6
Order By: Relevance
“…Smith et al 2016;Łokas 2020) have shown that infalling and orbiting haloes within galaxy clusters are disrupted by a series of processes which dominate in such environments, such as ram-pressure stripping (e.g. Bahé & McCarthy 2015;Arthur et al 2019;Mostoghiu et al 2021), mergers (e.g. Behroozi et al 2014;Lagos et al 2018a), or tidal torques (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smith et al 2016;Łokas 2020) have shown that infalling and orbiting haloes within galaxy clusters are disrupted by a series of processes which dominate in such environments, such as ram-pressure stripping (e.g. Bahé & McCarthy 2015;Arthur et al 2019;Mostoghiu et al 2021), mergers (e.g. Behroozi et al 2014;Lagos et al 2018a), or tidal torques (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…outside the central aperture) and thus they are prone to suffer from mass loss from processes that strip the halo at its outskirts. The gas component, on the other hand, is mostly gone regardless of their mass, as gas is affected by an entirely different set of processes as they fall into the central halo, that is to say ram-pressure stripping (Arthur et al 2019;Mostoghiu et al 2021). In studying the radial distribution of the gas inside infalling haloes (not shown here), we find that haloes that never reached the denser regions of the cluster halo are still considerably stripped of their gas component, which is in agreement with Power et al (2020), Arthur et al (2019), and Mostoghiu et al (2021).…”
Section: Mass Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the cluster backsplash galaxies [19,20] and shock radius [21] have also been well addressed. The advanced baryon models in hydrodynamic simulations allow us to perform a detailed investigation on the cluster properties, such as profiles [22,23], substructure and its baryonic content [24][25][26][27], dynamical state and morphology [28,29], cluster (non-)thermalization [30,31], the fundamental plane [32], and the cluster mass biases [33, for hydrostatic-equilibrium assumption], [34, for sigma-mass relation] and [35, for weaklensing]. Lastly, comparing to the void/field region runs in this project allows us to study the effect of environment [36]; including the self-interacting dark matter run allow us to constrain the dark matter cross-section [37]; It further help us to examine the chameleon gravity [38].…”
Section: In Prep)mentioning
confidence: 99%
“…On the other hand, the use of stacking to probe below detection limits suggests the existence of a population of cluster galaxies with low gas fractions and short depletion timescales (Betti et al 2019;Zavala et al 2019). Theoretically, evidence from cosmological simulations is mounting that gas loss should start at large radii, with significant depletion of the gas reservoir by or at first passage of the cluster center (Oman & Hudson 2016;Zinger et al 2018;Arthur et al 2019;Mostoghiu et al 2021;Oman et al 2021).…”
Section: Introductionmentioning
confidence: 99%